(untitled) (Indian Journal of Animal Production and Management, 2024)
Uttarakhand, a mountainous state located on the southern slope of the Himalayas, relies heavily on animal husbandry for its economy. However, the piggery sector in the state is unorganized and insufficient to meet the growing demand for pork. Moreover, the increasing urbanization and deforestation in the planar districts have blurred the boundaries between wildlife, livestock and human habitats. This study through a household survey approach aims to determine the socio-economic characteristics of the pig rearing community, the pig husbandry practices they adopt and also assess the ecological impacts of pig farming in urban districts of Uttarakhand. 28 households were surveyed and analysis of the result shows dismal socio-economic condition of the pig rearing community. Furthermore, 28.6% maintained breeding boar of feral origin and 96.94% followed semi-intensive pig rearing practices; hence human settlements have stayed in close association with pigs (domestic and wild) and other domestic animals. The possibility of the emergence of zoonotic disease and its easy transmission to humans has become more prominent in the urban setting. The findings of this study provide a preliminary picture of the current status of pig husbandry practices and challenges faced by piggery sector and government can take into account these crucial insights for a holistic piggery development program in the state.